An exploratory study on the information seeking behavior of litigation lawyers in the National Capital Region - Sipin, Ian Dominic P.; Obille, Kathleen Lourdes B. (Quezon City bSchool of Library and Information Studies, University of the Philippines Diliman, 2020)
Information seeking is crucial for the work of layers and legal professionals since it involves a great extent of information and knowledge. In the case of litigation lawyers, information is sought to substantiate the arguments to be made in a court or tribunal. The researcher sought to identify the process of litigation lawyers in conducting their research. what sources they use, and if there are circumstances where research may be forgone.

This study utilized a digitally administered questionnaire with open-ended questions to determine the daily work routines of the litigation lawyers-preparing to go to work, acting upon being assigned to a case, conducting legal research, ending a search, and making decisions on certain trade-offs-and their preference in information materials-print or non-print-and to what purpose to they use these materials.

It was found that (1) the respondents subscribe to the Information Search Process model of Kuhlthau and Information Seeking model of Leckie et al. while engaging in the monitoring process of Ellis et all., (2) they mostly use websites for non-print and textbooks and SCRA/Philippine Reports as print sources in conducting research (3) the respondents utilize both non-print and print sources but primarily use the former due to accessibility and portability, and (4) not all respondents have access to a law library albeit access is wanted, and the library is seen as the repository of information that is not available online.

In conclusion, for litigation lawyers, research is an essential component of their work. The utilization of a plethora of information sources in both print and non-print formats is a manifestation that legal research in aid of litigation is an activity done in an exhaustive manner. This research is also not done in solitude as the lawyers require the assistance of staff, paralegal, associates, and colleagues. The results of this research further substantiate the notion that legal is a knowledge-intensive field.
Thesis
Keywords: Information behavior; Litigation; Lawyers; Philippines -- National Capital Region